Government Policy in Ensuring Accessibility and Legal Protection of Health Rights for Persons with Disabilities - Dumako, Ananda Rayhan; Trisista, Ratna Galuh Manika (Fakultas Hukum Universitas Islam Jakarta, 2024)
People with disabilities often face major challenges in accessing equal health services, which are influenced by existing government policies. This research aims to analyze the policies adopted by several countries in realizing equal access to health for persons with disabilities, with a focus on the implementation of the Convention on the Rights of Persons with Disabilities (CPRD). The research method used is normative legal research method, with a statute approach and comparative approach. This approach is applied to examine government policies in Indonesia and several countries related to the fulfillment of health rights for persons with disabilities. The results show that although many countries have ratified the CPRD, the implementation of policies related to health accessibility still faces various challenges, including limited infrastructure, discrimination, and lack of training of medical personnel. In Indonesia, despite the existence of regulations such as Law No. 8/2016, the main challenges lie in public awareness and policy implementation on the ground. In conclusion, further efforts are needed to strengthen inclusive health policies, improve physical accessibility and training of medical personnel, and increase public awareness to ensure people with disabilities receive equal and discrimination-free health services.